The Effectiveness of the Taklim Assembly of Baitul Mizan Serang Kalikajar, Kalikajar District Wonosobo Regency in Improving the Quality of Faith and Takwa - Untaji Affan; Imron Imron (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Islam is a perfect religion, its Shari'a regulates the entire system of human life to achievea happy life in this world and in the hereafter. The perfection of Islamic teachings includesthe fields of aqidah, sharia, morality and muamalah, so that with that perfection throughthe holy book the Qur'an is conveyed gradually and the people accept Islamic da'wahgradually. The treasures of Islam are so deep and broad that they need to be conveyedwisely and full of example. Majelis Taklim is one of the educational institutions in thecommunity that was established from, by and for the community, to convey, teach,understand, practice Islamic teachings and provide examples. This activity is heldcontinuously, so that people who already have religion, beliefs and customs can accept andpractice the teachings of Islam. Therefore, the taklim assembly has different forms, seenfrom the participants, the time of implementation, the method, the material. By notdenying the efforts of religious leaders and administrators of the Baitul Mizan mosque,Serang Village, Kalikajar Village, Kalikajar District, Wonosobo Regency, that the taklimassembly is faced with the condition of human resources that are less able to adapt to theneeds of the target group so that the taklim assembly has not been maximized in an effortto increase faith and piety to Allah. . Judging from the readiness of human resources toaccept change, and the use of existing media (mosques) to compete in goodness.